The perfumist of Paris [compact disc, unabridged] - Joshi, Alka (Joshi, Alka. Jaipur trilogy., 2023)
Immersed in her exciting perfume work, Radha hears that her unacknowledged son is coming to Paris to find her, which could upset her career and threaten to destroy a vulnerable marriage.